Stem cell-based therapies for temporomandibular joint osteoarthritis and regeneration of cartilage/osteochondral defects: a systematic review of preclinical experiments. Issue 9 (September 2022) - Matheus, H.R.; Özdemir, Ş.D.; Guastaldi, F.P.S.
Summary: Objectives: The aim of this systematic review was to assess the effects of stem cell-based therapies on the treatment of Temporomandibular Joint Osteoarthritis (TMJ-OA) and the regeneration of cartilage/osteochondral defects. Methods: Data on preclinical studies evaluating the effectiveness of stem cell-based therapies for treating Temporomandibular Disorders (TMDs) were extracted from PubMed, Web of Science, and Cochrane Library and the grey literature by three independent reviewers. A manual search was performed in the databases, the reference list of review studies, and relevant journals in the field. Compliance with the ARRIVE guidelines was evaluated for quality assessment. SYRCLE's risk of bias tool for animal experimental studies was assessed to define internal validity. Results: After applying the inclusion and exclusion criteria, 10 studies were included in the qualitative synthesis. Regardless of cell origin, stem cell-based therapeutic approaches induced protective, anti-inflammatory, and chondroregenerative potential in the treatment of TMJ-OA. Regeneration of the cartilage layer on the surface of the condyle was achieved when stem cells were directly flushed into the defect or when delivered within a carrier. Conclusion: Stem cell-based therapies may be considered a promising approach for the treatment of TMJ-OA and for the regeneration of full-thickness cartilage and osteochondral defects in the TMJ. Human studies shall be performed to validate these results found in animals.